2007
DOI: 10.1038/sj.bjp.0707518
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of thromboxane receptors by diclofenac and lumiracoxib

Abstract: Background and purpose: Non-steroidal anti-inflammatory drugs (NSAIDs) are analgesic and anti-inflammatory by virtue of inhibition of the cyclooxygenase (COX) reaction that initiates biosynthesis of prostaglandins. Findings in a pulmonary pharmacology project gave rise to the hypothesis that certain members of the NSAID class might also be antagonists of the thromboxane (TP) receptor. Experimental approach: Functional responses due to activation of the TP receptor were studied in isolated airway and vascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It has been reported that lumiracoxib is not only a COX‐2 inhibitor, as it also exhibits activity as a thromboxane receptor antagonist in the micromolar concentration range (Selg et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lumiracoxib is not only a COX‐2 inhibitor, as it also exhibits activity as a thromboxane receptor antagonist in the micromolar concentration range (Selg et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration by Selg et al . that both a tNSAID (e.g., diclofenac) and a highly selective COXIB (e.g., lumiracoxib) possess the previously undescribed pharmacological profile of competitive antagonism at the TP receptor may provide the basis to hypothesize a novel class of safer NSAIDs (third generation) and to plan highly innovative studies of structure‐activity relationship, chemical synthesis, and pharmacological investigations …”
Section: Cyclooxygenase Products and Cardiovascular Pathophysiologymentioning
confidence: 99%
“…Ramatroban, a TP antagonist recognized to inhibit platelet aggregation induced by collagen and U46619 [20] . Diclofenac, a non-steroidal anti-inflammatory drug (NSAID), concentration dependently and selectively inhibited TP mediated contraction in smooth muscles as well as human platelet aggregation [21] . The fourth compound we tested was L-670596, a potent TP antagonist in human platelets and shown to inhibit contraction in guinea pig tracheal rings in a concentration dependent manner [22] .…”
Section: Introductionmentioning
confidence: 99%